Analysis of the Influence of Digital Marketing and Facilities on Parents' Decision to Enrol Their Children at Playfield Elementary School Jakarta with Brand Image as the Intervening Variable - Andrian F. A. Tarigan; Theresia Pradiani; Fathorrahman Fathorrahman (Publikasi Indonesia, 2024)
This study aims to examine the influence of Digital Marketing and Facilities on the Decision to enrol children at SD Playfield Jakarta, with Brand Image as the mediating variable. Data were collected from 33 respondents who are parents of students at SD Playfield Jakarta using the purposive sampling technique. The results of the multiple regression analysis indicated that Digital Marketing (t = 0.188, p = 0.852) and Facilities (t = -0.630, p = 0.534) did not have a significant influence on Brand Image. However, Brand Image demonstrated a significant positive impact on the Decision to enrol children (t = 3.498, p = 0.002). The coefficient of determination showed that 37.2% of the variability in enrolment decisions can be explained by Digital Marketing, Facilities, and Brand Image. The F-test indicated that the overall regression model is significant (F = 5.718, p = 0.003). In conclusion, while Digital Marketing and Facilities may not directly affect Brand Image, enhancing Brand Image can positively influence parents' decisions to enrol their children at SD Playfield Jakarta. It is recommended that the school strengthen its marketing strategies and improve facilities to enhance its Brand Image, thereby supporting increased parental enrolment decisions